The Role of Social Networks in Strengthening Market Access and Distribution of Organic Agricultural Products - Malta (Global Writing Academica Researching and Publishing, 2025)
Organic farming continues to grow rapidly, driven by growing public awareness of health and environmental sustainability. However, significant challenges remain, including limited market access and product distribution, which often fall short of increasing demand. Furthermore, the emergence of social networks in the digital era opens up new opportunities to strengthen connections between farmers, consumers, and various stakeholders in the organic agricultural supply chain. This study aims to analyze the role of social networks in expanding market access and strengthening the distribution of organic agricultural products through the use of digital technology. The research method employed a qualitative approach, employing literature analysis, data collection from secondary sources, and exploring social network optimization practices implemented in the organic agricultural sector. The analysis identified shifts in social interactions resulting from digital transformation and opportunities for integrating traditional networks with technology-based networks. The results indicate that digital social networks can expand the marketing reach of organic agricultural products more quickly, efficiently, and effectively. The integration of digital community applications plays a crucial role in building close relationships between farmers and consumers, thereby increasing trust and loyalty. Changing interaction patterns within social networks also encourages the creation of new distribution models that are more adaptive to market needs. Therefore, optimizing social networks in the digital era is a key strategy for strengthening the sustainability and competitiveness of organic agricultural products in the modern marketplace.